Model Kooperatif Tipe Teams Games Tournaments (TGT) pada Pembelajaran Materi Trigonometri untuk Meningkatkan Aktifitas dan Prestasi Belajar Siswa SMAN 3 Selong - Muhammad Juaini (Journal on Education, 2023)
This study aims to determine the application of the TGT type learning model in increasing student activity and learning achievement on the subject matter of trigonometry in class X MIPA-3 SMAN 3 Selong. with 36 students. This type of research is Classroom Action Research which consists of planning, implementing, observing, evaluating and reflecting. The results showed that students were more active in the teaching and learning process and there was an increase in mathematics learning achievement of class X MIPA-3 students of SMAN 3 Selong by applying a TGT-type cooperative model to learning the subject mattertrigonometry. This increase in achievement is seen from the increase in the percentage of student learning completion classically in cycle I with classical completeness of 65.71%, cycle II with classical completeness of 76.47% and in cycle III with classical completeness of 90.09%. In addition, after implementing with the TGT-type cooperative model, student learning activities increase each cycle with active, active, and very active criteria. From the results of this study, it can be concluded that the application of the TGT type cooperative model to the learning of trigonometric subject matter can increase the activity and learning achievement of class X MIPA-3 students of SMAN 3 Selong.